2020
DOI: 10.3390/fermentation6010035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrient Supplementation on Torulaspora Delbrueckii Wine Fermentation Aroma

Abstract: This study was performed with the aim of characterizing the fermentative performance of three commercial strains of Torulaspora delbrueckii and their impact on the production of volatile and non-volatile compounds. Laboratory-scale single culture fermentations were performed using a commercial white grape juice. The addition of commercial nutrient products enabled us to test the yeasts under two different nutrient conditions. The addition of nutrients promoted fermentation intensity from 9% to 20 % with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Measurements of the non-volatile organic acids, ethanol, and residual sugars were performed by high-performance liquid chromatography (HPLC) according to Kanter et al, 2020 [ 26 ]. For the analyses of the esters, higher alcohols, and fatty acids, the method of the Department of Microbiology and Biochemistry of Hochschule Geisenheim University [ 27 ] was applied. The concentrations of acetaldehyde and pyruvate at the end of the fermentations were measured using specific enzymatic assays (K-ACHYD and K-PYRUV, Megazyme, Butzbach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of the non-volatile organic acids, ethanol, and residual sugars were performed by high-performance liquid chromatography (HPLC) according to Kanter et al, 2020 [ 26 ]. For the analyses of the esters, higher alcohols, and fatty acids, the method of the Department of Microbiology and Biochemistry of Hochschule Geisenheim University [ 27 ] was applied. The concentrations of acetaldehyde and pyruvate at the end of the fermentations were measured using specific enzymatic assays (K-ACHYD and K-PYRUV, Megazyme, Butzbach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, studies conducted on a pilot scale that includes sensory analysis of the reduced alcohol wines made from non-Saccharomyces yeasts is lacking. Nitrogen management is an important factor to achieve ethanol reduction, which has been highlighted by authors in previous studies [126,127,131]. The specific nutrient needs of non-Saccharomyces yeasts used for ethanol reduction purposes should be further studied.…”
Section: Other Non-saccharomyces and Saccharomyces Non-cerevisiae Yeastsmentioning
confidence: 97%
“…Recent studies showed that the nutrient supplementation has a positive correlation on the ethanol yield of T. delbrueckii [126,127]. Additionally, Mecca et al [127] studied three commercially available T. delbrueckii strains and compared some oenological characteristics. Significant differences were reported in ethanol yields, as well as in the volatile aroma compounds [127].…”
Section: Torulaspora Delbrueckiimentioning
confidence: 99%
See 1 more Smart Citation
“…The final concentrations of the major organic acids, sugars, and ethanol were determined by HPLC, using a method according to Schneider et al [ 59 ] and modified as described in [ 60 ]. An HPLC Agilent Technologies Series 1100, equipped with a binary pump, an autosampler, a multi-wavelength detector (MWD), and a refractive index detector (RID, Agilent Technologies, Steinheim, Germany) was employed.…”
Section: Methodsmentioning
confidence: 99%